Development of Android-Based Interactive Multimedia in E-Learning - Azizah, Alif Luthvi; Destini, Frida; Hariyanto, Hariyanto (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The utilization of digital media in e-learning has become one of the alternatives to conduct teaching and learning activities more efficiently when faced with challenges such as long distances, a lack of physical learning spaces, shifts in class schedules, and so on. One of the innovations in e-learning is the development of multimedia learning materials that can optimize the learning process and output. The research aims to develop interactive multimedia learning media based on Android for e-learning. The research method used is a development-research, which includes: 1) Research and information collecting; 2) Planning; 3) Developing a preliminary form of product; 4) Preliminary field testing; 5) Main product revision; 6) Main field testing; 7) Operational product revision; 8) Operational field testing; 9) Final product revision; 10) Dissemination and implementation. The product was tested in a class G PGSD (Elementary School Teacher Education) at FKIP University of Lampung with 34 students. Based on the research results, the Android-based interactive multimedia developed was found to enhance students' cognitive skills, with an N-gain score of 0.729, categorized as "High". The implications of this research indicate the importance of utilizing technology in developing instructional media. The positive outcomes of using Android-based interactive multimedia in enhancing students' cognitive skills can serve as a basis for further studies aimed at creating engaging, innovative, and enjoyable learning experiences.